PHILOSOPHY OF WOMEN'S MOVEMENT IN THE CONTEXT OF FEMINISM - B. S. Ganganalli (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The word movement itself symbolizes mobility and change. There have been many movements in this world. From the freedom movement to the Gokak movement, from the film distributors' demonstration to opposing globalization, from protesting price hikes to condemning the war-mongering policy of America.... The women's movement is one of the movements that have spread widely in history. It is, in a sense, very recent. In a sense, it is also very ancient. This is an attempt to look at the women's movement that has spread from the Sharana movement in which Akka Mahadevi also participated to today's Women's Reservation Bill, in the context of feminism. The illusion or hope that this might lay a solid foundation for the women's movement is making me think in this direction.